Hazard analysis and critical control point of milkfish floss production as indigenous food from Banten province. Issue 1 (March 2021) - Nurtiana, W; Najah, Z; Anggraeni, D; Putri, N A
Abstract: Milkfish floss is indigenous food from Banten which is produced by Small and Medium Enterprise (SME). Milkfish floss is potential to be developed due to the high demand from outside Banten areas, but it is very easy to get rancidity, spoilage by the microbes, or existing dust and hair. Therefore, milkfish floss production process still needs to improve the processing method according to the standards to produce a safe and good product. Quality assurance is done by compiling hazard analysis and control point (HACCP) documents. The aim of this study was to identify hazards of raw material and production chain, determine CCPs in every chain, and create HACCP document plan. The research method was conducted by interview, observation, laboratory analysis, and literature review. The compiling of the HACCP document is carried out in several steps including creating a HACCP team, identification of consumers and product descriptions, making processing flow diagrams, identifying hazards, determining critical control points (CCPs), determining the critical limit, monitoring, and correcting action. The hazards that may occur in milkfish floss are residues of heavy metals, pathogenic microbes, thorns, dust, and hair. The CCPs of raw material are fish, lemongrass, lime leaves, shallot, and garlic, while the CCPs of the processing are the acceptance of fish, cleaning, steaming, frying, draining, and packaging.